What do medical students think about primary care in Malaysia? A qualitative study - Ng, C.J.; Leong, Kwok-Chi; Teng, Cheong-Lieng (2005)
In Malaysia, there has been a recent shift in emphasis from secondary care to primary care, both in terms of healthcare as well as medical education. However, general practice is not considered as a desirable career path and less than 1 of general practitioners (GPs) are trained. This could be due to many factors, one of which is the perception of primary care among medical students during their undergraduate training. This study aimed to look at the perceptions of medical students towards primary care and their influencing factors. Thirty-three final-year medical students participated in six focus group discussions at two universities in Malaysia in 2003. Participants were recruited by snowballing, taking into account the participants' gender, ethnicity and social background. The results of this study showed that there were mixed perceptions about primary care as a discipline. Understanding of the discipline, role-modelling of doctors, disparity between training and practice were highlighted as significant influencing factors. Lack of understanding of the discipline still exists among the medical students. Understanding their perceptions and the underlying influencing factors will allow educators to find ways to improve the students' attitudes towards the discipline.